The Influence of Competency on Employee Performance at Public Security and Order Supervising Officer, Central Lombok Police - Permana, I Putu Agus Indra; Indriati, Fibria (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2024)
This research aims to determine the relationship and influence between Competency and Performance of Bhabinkamtibmas police officers. The research was carried out using a quantitative approach by collecting data using a questionnaire from 103 Bhabinkamtibmas officers from a total of 139 officers. The questionnaire used has met the Validity and Reliability criteria very well. The results of the analysis carried out show that there is a significant relationship and influence of Competency on Performance. The influence value (R-Square) obtained was 0.768 or 76.8%, which is included in the strong category. This value shows that Competency is able to predict variations in Performance of 76.8% while the remaining 23.2% is predicted by other variables not used in the model. The regression equation obtained is Y = 0.613 + 0.846X, indicating that for every 1 point added to X, Y will increase by 0.846. In general, it can be concluded that to improve the performance of Bhabinkamtibmas, competency increases are needed and it would be very good if this improvement was carried out consistently to maintain the performance of Bhabinkamtibmas officers.